Social pressure factors aimed at football referees in Turkey - ZELYURT, MERT KEREM; ŞAŞMAZ ATAÇOCUĞU, MUAZZEZ (My University, 2022)
In this study, the football fans, club managers, coaches, football players and sports media have been problematized as various kinds of social stress elements against the referees. The objective of the study is to find out the most dominant social stress elements on the referees of the two minor Professional leagues and the amateur league. The implementation of the study includes questionnaire and depth interview data. In the training of the referees from the county of Istanbul in April,2014, 55 referees in total were conducted a questionnaire. The data acquired from that are evaluated at SPSS statistics program. The in depth interviews made with 9 referees have been subjected to content analysis.